Therapeutic potential of bacteriophages against methicillin-resistant Staphylococcus aureus - Ilbay-Mayta , Jennifer Elizabeth (2024)
Antimicrobial resistance is a phenomenon in which microorganisms such as bacteria become resistant to drugs that were previously effective in eliminating or controlling their growth. According to the WHO, one of the priority pathogens needing an alternative therapy is methicillin-resistant Staphylococcus aureus (MRSA), due to its numerous pathogenic mechanisms, its ability to synthesize bioflms, and its unique clonal variation that allows it to spread and colonize new environments. Phage therapy has shown a broad approach to treating infections caused by this pathogen, given its high specifcity and effectiveness in killing the host bacteria. However, there are still some obstacles to its therapeutic use inhumans, requiring more clinical trials. This research article details cases and clinical studies that provide useful information, which can be complemented by subsequent clinical studies.